Damascus tiles : mamluk and ottoman architectural ceramics from syria - Millner, Arthur; Canby, Sheila R. ([S.l.] : Prestel, 2015)
One of art history's previously overlooked treasures--the vibrant ceramic tiles of Syria and especially Damascus--are the subject of this fascinating study by a leading Islamic art expert. Architectural ceramic decoration is one of the most celebrated manifestations of the arts of Islam. Spanning a period from the 13th to the 20th century, the tiles featured in this book exhibit a rich range of influences from Persia, Turkey, China and even Europe. A renowned specialist in the fields of Islamic and Indian art, Arthur Millner explores the historical context that allowed the uniquely creative achievement of Syrian craftsmen to flourish, and why tiles from this region are less restricted in artistic expression than those from better-known centers of production. The complex and interconnected nature of tile designs, techniques and color palettes is explored, highlighting what is distinctive about Damascus ceramics and how they relate to tiles produced in other parts of the Islamic world. Finally, the author traces the journey made by many of these tiles to the West, embellishing the interiors of wealthy clients as Islamic art became both fashionable and influential in late-19thcentury art and design.
Introduction -- Historical background -- The mamluk period -- The ottoman period -- Awestern craze for titles -- An anthology damascus titles -- NOTES -- Biblliography --Maps --Glossary --Picture credits -- Index
engineering bookfair2016
includes bibliography
Keywords: Tiles -- Syria; Decoration and ornament, Architectural -- Syria